Experimental determination of the efficiency of indigenous and exotic natural enemies of the cassava mealybug, Phenacoccus manihoti Mat. Ferr. (Hom., Pseudococcidae), in Ghana - Cudjoe, A.R.; Neuenschwander, Peter; Copland, M.J.W. (Wiley, 1992)
The efficiency of natural enemies, especially the exotic parasitoid Epidinocarsis lopezi (De Santis) and the indigenous predator Exochomus troberti Mulsant, in reducing populations of the cassava mealybug (CM), Phenacoccus manihoti Mat.‐Ferr., was studied through exclusion experiments. In the physical exclusion experiment lasting 52 days, CM numbers on tips in open sleeves, where access by natural enemies was allowed, were on average 43 times lower than on infested tips enclosed by a sleeve cage. In comparison to the situation in closed sleeve cages with CM only, host densities were reduced by only 3.9 and 1.4 times, where E. lopezi and coccinellid larvae, respectively, had been added. In the chemical exclusion experiment, mealybug numbers increased continuously up to the end of the experiment, after nine weeks, reaching 694 CM per group of 10 tips treated with insecticide, as compared to between 11.5 and 19.6 CM on the same unit of plants sprayed with water.